Improving the organizational communication of the management team - Menor, Majean R. (Animo Repository, 2021)
This Integrative Action Research paper’s primary focus is to improve the organizational communication of ABC, Inc’s management team by providing them training and guidelines on how to communicate effectively. Using first, second, and third-person inquiry, my collaborators and I were able to dig deeper into the issue of poor communication and provide a proper resolution to benefit the company and the employees. Guided predominantly by Lewin’s change management model, and Berlo’s SMCR Model of Communication, we embarked on 2-cycle action research to address the issue of poor communication. For the first cycle, we provided communication training to the management team to help the management team acquire new skills, sharpen existing ones, increase productivity, perform better, and be better at communicating with our clients. For the second cycle, we uploaded an online guideline to our management system that the management team can review and use. By providing an online guideline, we believe that it will greatly help the management team in accomplishing their tasks and effectively communicating with our clients. It is like providing online learning from the comfort of their home. One of my key takeaways from this action research is the importance of communication and collaboration. Effective communication can eliminate unnecessary problems. As per collaboration, when individuals work together, processes and goals become more aligned, leading the organization towards a higher success rate of achieving a common goal. The outcomes mentioned in this action research prove that communication and collaboration in an organization is a critical contributor to overall organization’s success.